Caregiver burden in the care of the elderly - Suriawati Ghazali
Background of the study: As Malaysian's elderly populations grows, this will increase the number of elderly people with health problems that prevent them for caring for themselves and forcing them to dependence on others. This means more caregivers are needed by older adult to assist them in their ADLs. AS nonprofessional, most family caregivers have very little training in providing caregiving, but they frequently perform many tasks once accomplished by a registered nurse with specialized education. Objectives of the study: The objective of this study was to determine the level of dependence of the elderly and the burden of caregiver who care of the elderly with chronic illness in a Tertiary Referral Centre. This study aims to identify the level of burden and types of burden perceived by the caregivers who care of the elderly with chronic illness. Materials and Methods: A descriptive cross-sectional study was conducted among 200 caregivers who care of the elderly person attending the outpatient medical clinic in tertiary Referral Centre. The samples were recruited by using the convenience sampling method. The questionnaire used consists of four components; demographic questionnaire, caregiver burden inventory scale, and the modified Barthel's Activity of Daily Living Scale. All participants was signed a consent form, giving the researcher permission to use the data that was provided. SOSS windows version 16, non - parametric test and inferential data analysis were used to analyse data to address research objectives of the study. Findings: The finding shows that 66.5% of elderly were dependent in at least one activity of daily livings. The most common type of functional dependence among the elderly were climbing stairs, walking and transferring. The level of burden of the caregiver was at low level which 81% was reported low level of burden while remaining 19% was reported high level of burden. As regard of type of burden, time-dependence burden was reported higher than physical and emotional burden. Only employment status and elderly level dependency give statistically significant interaction or confounding brought in the significant relationships with the level of burden as (P<0.05; p<0.001). Conclusions: Findings suggest that the focus of intervention should be helping caregivers to practice effective time-management, effective coping strategies, seeking for support networks and present respite care as enabling the caregiver to get some breaks from caregiving activities.